Thoreau's sense of place : essays in American environmental writing - Schneider, Richard J. (American land and life series., 2000)
Recent Thoreau studies have shifted to an emphasis on the green" Thoreau, on Thoreau the environmentalist, rooted firmly in particular places and interacting with particular objects. In the wake of Buell's Environmental Imagination, the nineteen essayists in this challenging volume address the central questions in Thoreau studies today: how "green," how immersed in a sense of place, was Thoreau really, and how has this sense of place affected the tradition of nature writing in America?